Comparison of polymer types on physical evaluation of in situ ophthalmic gel preparations: A Review - Putra, Hasan Etanov; Zahra, Aliya Azkia; Aini, Kania Nurul; Rafifa, Muthia; Maulida, Verin Sakinah; Sabrina, Lina Maisa (Jurnal Pijar Mipa, 2025)
The development of temperature, pH, and ion-responsive in situ ophthalmic gels aims to enhance drug retention and release efficacy in the eye. Polymers such as Poloxamer (thermosensitive), Gellan Gum (ion-sensitive), and Carbopol (pH-sensitive) exhibit adaptive gelation mechanisms suited to ocular physiological conditions. Poloxamer forms a gel at body temperature, prolonging drug contact duration, while Gellan Gum creates a stable gel network through ionic interactions with lacrimal fluid, increasing viscosity and extending drug release. Carbopol, which transitions into a gel at neutral pH, provides optimal viscosity stability in the ocular environment. This study employs a literature review method, gathering data from indexed journals and scientific publications over the past 10 years. Evaluation results indicate that a combination of Gellan Gum and Methacrylated Gellan Gum at a concentration of 0.6% w/v yields the highest viscosity and encapsulation rate, with a contact time of up to 8 hours, making it an excellent formulation for long-term ophthalmic applications. This paper highlights the significant potential of in situ gels as drug delivery systems, optimizing ophthalmic therapy by enhancing drug viscosity and encapsulation stability.